Recomendações Pedagógicas para Desenvolvimento de Ambientes Virtuais de Aprendizagem, Construcionistas, para Surdos, na Perspectiva do Usuário - Campos, Magaly Liliane Chaves (Universidade Federal do Tocantins, 2019)
The inclusion of the deaf into regular classes is widely guaranteed on laws, but to make it effective, investments in specific curricula, methods, techniques, educational resources, and organization are necessary. Considering the specificity of the language of the deaf, visual-gestural, digital resources can favor the knowledge construction by deaf students, since they meet the specificities of that community. The objective of this research is to identify and present pedagogical requirements for the development of virtual learning environments for deaf secondary school students. In view of the greater importance of the deaf learner, a learning theory has been chosen that has the student as an active subject of the knowledge construction and that has the computer as a learning tool, thus, discarding instructional theories of learning. Considering the qualitative research nature, we opted for the methodological use of focus groups with deaf students and an integrative review of literature on educational software developed for educational purposes for deaf users. In spite of the varied categorizations of pedagogical requirements, this work emphasized the categories: user’srequirements/expectations, learning theory, content quality, comprehensiveness and completeness of content and content presentation. As a result, this work presents 30 pedagogical requirements for the construction of digital environments for the learning of deaf students.